Agglomeration and clusters near and far for regional development: A critical assessment. Issue 3 (20th March 2020) - Gordon, Peter; Kourtit, Karima
Abstract: The aim of the paper is to elaborate the popular concept of spatial clusters in a broader regional development context. Are regional clusters natural and emergent? Do we understand how and why? Does the concept necessarily imply nearness? How much? How little? Is there a role for policy makers? This contribution offers an up‐to‐date critical perspective. Resumen: El objetivo del artículo es tratar en más detalle el concepto popular de los conglomerados espaciales ( clusters ) en un contexto de desarrollo regional más amplio. ¿Son los clusters regionales naturales y emergentes? ¿Se entiende cómo y por qué? ¿Implica el concepto necesariamente la cercanía? ¿Qué tanto? ¿Qué tan poco? ¿Existe una función para la formulación de políticas? Esta contribución ofrece una perspectiva crítica actualizada. 抄録: 本稿の目的は、空間的クラスターの一般的な概念について、地域開発の大きな視点から詳しく説明することである。地域クラスターは自然発生的かつ新たに出現したものか、それがどのように、なぜなのかは解明できるか、その概念は必ず類似性を包含するものか、それはどの程度包含するか、包含しないのか、政策立案者に役割はあるのか、といった問題を検討する。また、最新の批評的視点を提示する。